Marital Interference on Academic Activities of Adult and Non-Formal Education Learners: A Study of Women Centres for Continuing Education in North-West, - Murtala Akanbi Yusuf; Iquo Okon Mkpa (Universitas Negeri Semarang, 2025)
Despite the centrality of women education in the development of societies, a huge gender gap still exists in education in northern Nigeria, at the detriment of women and girls. The gender disparity in education is induced by a matrix of forces, ranging from poor and negative parental attitude towards the education of the girl child, to stereotyping of girls in the society, leading to high illiteracy among married women and huge school drop-outs. Inspired by the imperative to address the gender concerns, this study investigated the impact of marital responsibilities on the academic activities of married women in Continuing Education Centres in North-west Nigeria. A descriptive survey design was used. A sample size of 306 married women and 152 women without marital status was selected using systematic and stratified sampling techniques. Two instruments (Marital Induced Academic Challenges Questionnaire (MIACQ) and End of Session Examination Scores and were used for data collection. The data collected were analysed using frequency and percentages and t-test. The findings revealed that the inability of married women to relate easily with other learners, inadequate time to do homework without interruption, poor reading skills, and absenteeism in tutorials are some of the academic challenges facing married women as learners. The study concluded that the challenges that emanated from being married women and learners have led to poor academic performance and stress among married women. The maturity displayed by married women learners in coping with the stress of marital and academic responsibilities must be strengthened particularly in the area of development of plan action by the learners themselves. The study recommended that adult and non-formal education programmes such as regular orientation and counseling for both learners and their teachers should be popularized